Determinação dos níveis liquóricos de gaba, aminoácidos neurotransmissores e outros em pacientes esquizofrênicos crônicos - Diniz, José Tarcizio (1990)
The GABA liquoric levels and other aminoacids was quantifyied in paranoic and simple schizophrenic patients according to the International Code of Diseases (I.C.D-9), chronics between 5 to 10 years of evolution an between 18 to 45 years old. Mental healthy persons were the control 'í- group.'It was found in the schizophrenic patients an enhance of GABA liquoric levels (P 0,001), taurine (P < 0,01) . arginine (P < 0,01), alanine (P < 0,05) and leucine (P < 0,005). The GABA and aminoacids dosage was made with an aminoacid microanalyser (that was built in our laboratory) with the sensibility of 1 nmol, according with HARE'S Method (Methods in Enzimology, Vol. XLVII, pp 3-18) modifyed. Our results are in compliance with a possible Gabaergic hiperreativity in the chronic schizophrenia and coincide with that presented by (McCARTLY et al (1981) and VAN KAMMEN et al (1982) . The taurine possibly is also implicated in the modulation of GABA-Dopamine. It's possible to suggest Dopamine-Gabaergic hipotesis to the schizophrenia.